1999
DOI: 10.1111/j.1600-0404.1999.tb00664.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of increased levels of soluble vascular cell adhesion molecule-1 (SVCAM-1) in the cerebrospinal fluid of patients with multiple sclerosis and systemic lupus erythematosus

Abstract: The concentration of soluble vascular cell adhesion molecules (sVCAM-1) of serum and cerebrospinal fluid (CSF) was measured in clinically selected multiple sclerosis (MS) and systemic lupus erythematosus (SLE) patients, using an ELISA assay. The mean sVCAM-1 concentration in the serum of SLE patients was higher than normal. The mean CSF sVCAM-1 concentration was increased in the MS as in the SLE group. On analysis, the data suggests that there are some similarities in the immunological effects of these two dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…We found elevated levels of ICAM-1, VCAM-1 and E-selectin in our cohort of SLE patients as compared to normal control values. Others studies have also detected elevated levels of one or more of these when compared to controls (16,18,20,21,23,24,(32)(33)(34)(35)(36). High levels of all soluble adhesion molecule levels were found in Mexican American lupus patients, as compared with Caucasian and African American lupus patients and Mexican American control subjects.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…We found elevated levels of ICAM-1, VCAM-1 and E-selectin in our cohort of SLE patients as compared to normal control values. Others studies have also detected elevated levels of one or more of these when compared to controls (16,18,20,21,23,24,(32)(33)(34)(35)(36). High levels of all soluble adhesion molecule levels were found in Mexican American lupus patients, as compared with Caucasian and African American lupus patients and Mexican American control subjects.…”
Section: Discussionmentioning
confidence: 95%
“…These findings support two other small studies that found a relationship between soluble adhesion molecule levels and neurological disease. Baraczka and colleagues previously described the appearance of new neurological symptoms in association with an increase in serum sVCAM-1 levels (18). Spronk and colleagues also found elevated levels of sVCAM-1 in 7 patients with some type of CNS involvement (22).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Because VCAM-1-deficient mice die during embryogenesis (77,78), it is impossible to perform experiments using gene knockout animals. Increased sVCAM-1 is found in the serum and synovial fluid of patients with RA (79)(80)(81), the serum of patients with primary antiphospholipid syndrome (APS) or APS in conjunction with systemic lupus erythematosus (SLE) (82), and the cerebrospinal fluid of patients with SLE and multiple sclerosis (83). Elevated serum concentrations of sVCAM-1 correlate strongly with disease activity in lupus nephritis (84,85).…”
Section: Vcam-1 and The Pathogenesis Of Ramentioning
confidence: 99%